Detection of co-colonization with Streptococcus pneumoniae by algorithmic use of conventional and molecular methods. Issue 5 (29th January 2015) - Saha, Sudipta; Modak, Joyanta K.; Naziat, Hakka; Al-Emran, Hassan M.; Chowdury, Mrittika; Islam, Maksuda; Hossain, Belal; Darmstadt, Gary L.; Whitney, Cynthia G.; Saha, Samir K.
Abstract Detection of pneumococcal carriage by multiple co-colonizing serotypes is important in assessing the benefits of pneumococcal conjugate vaccine (PCV). Various methods differing in sensitivity, cost and technical complexity have been employed to detect multiple serotypes of pneumococcus in respiratory specimens. We have developed an algorithmic method to detect all known serotypes that preserves the relative abundance of specific serotypes by using Quellung-guided molecular techniques. The method involves culturing respiratory swabs followed by serotyping of 100 colonies by either capsular (10 colonies) or PCR (90 colonies) reactions on 96-well plates. The method was evaluated using 102 nasal swabs from children carrying pneumococcus. Multiple serotypes were detected in 22% of carriers, compared to 3% by World Health Organization (WHO)-recommended morphology-based selection of 1 to 3 colonies. Our method, with a processing cost of 87, could detect subdominant strains making up as low as 1% of the population. The method is affordable, practical, and capable of detecting all known serotypes without false positive reactions or change in the native distribution of multiple serotypes.